Pengaruh Enterprise Risk Management, Kualitas Audit Eksternal Dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Maris Gihon Juventus Togatorop; Murtanto Murtanto (Pusat Riset dan Inovasi Nasional, 2024)
The era of globalization is marked by all companies being able to maintain their business amidst challenges and economic dynamics by maintaining stability and increasing company value. Companies are expected to always experience an increase in company value. In reality, most companies in Indonesia have small company values ​​and experience fluctuations from year to year. Fluctuations in company value which sometimes rise or fall too far can cause problems, such as the company losing its attractiveness in the world. stock market